Linseed oil and coconut oil in broiler feed (International Seven Journal of Multidisciplinary, 2023)
The objective of this study was to evaluate the effect of the inclusion of 1% of linseed oil and 1% of coconut oil in broilers feeding from one to 21 days, on the performance and serum biochemical levels of cholesterol and triglycerides. A total of 75 male, one-day, Cobb-type chicks were used. Distributed in a completely randomized experimental design, with three treatments and five replicates and five birds per experimental unit. The birds were housed in galvanized wire cages measuring 0.90m x 0.60m x 0.45m. The use of linseed and coconut oils did not influence weight gain and feed intake, but increased feed conversion over a period of one to seven days. In the period from one to 14 days only the feed intake was influenced by the inclusion of the oils. There was no significant effect on performance in the period from one to 21 days of life. Serum levels of cholesterol and triglycerides were reduced with the use of coconut oil. It is concluded that the use of linseed or coconut oils can be used to feed broiler chickens from one to 21 days, as it does not interfere with the final performance of the birds, and the inclusion of coconut oil benefits the health of the birds reducing the levels cholesterol and triglycerides. DOI: 10.56238/isevmjv2n1-007